2012
DOI: 10.1074/jbc.m112.346411
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Modern Glucocorticoid Cross-pharmacology Using Ancestral Corticosteroid Receptors

Abstract: Background: Drugs that target steroid receptors are notoriously promiscuous, causing an array of off-target side effects. Results: Reversal of the historical mutation H853R in the mineralocorticoid receptor (MR) fully restores agonist activity by mometasone furoate, an MR antagonist. Conclusion: A single residue outside of the ligand-binding pocket toggles agonism versus antagonism response by MR to synthetic ligands. Significance: Ancestral proteins are ideal tools to elucidate the mechanisms of drug selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Thornton and coworkers have generated crystal structures of ancestral proteins that along branches of a phylogenetic tree show conserved and changed binding functions. 3538 While the structures are of complexes rather than unbound, comparisons of the normal modes and RMSD of the static structures can be evaluated along a branch estimated as 0.10 substitutions per site without a change of binding partner and along a branch with length 0.14 substitutions per site with a change of binding partner. The first branch shows a static RMSD of 0.51 Å and a normal modes overlap of 0.72.…”
Section: Resultsmentioning
confidence: 99%
“…Thornton and coworkers have generated crystal structures of ancestral proteins that along branches of a phylogenetic tree show conserved and changed binding functions. 3538 While the structures are of complexes rather than unbound, comparisons of the normal modes and RMSD of the static structures can be evaluated along a branch estimated as 0.10 substitutions per site without a change of binding partner and along a branch with length 0.14 substitutions per site with a change of binding partner. The first branch shows a static RMSD of 0.51 Å and a normal modes overlap of 0.72.…”
Section: Resultsmentioning
confidence: 99%
“…MR is highly homologous to glucocorticoid receptor (GR) and both receptors are ligand-dependent transcription factors (Arriza et al, 1987; Kohn et al, 2012). MR and GR share 94% primary sequence homology in the DNA binding domain, and both receptors share the same HREs in several genes, including αENaC (Arriza et al, 1987; Chen, 1999; Mick et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of mometasone furoate, it was found that there is a dipole–dipole interaction between the C21 Cl and an asparagine residue in the binding pocket AncGR2-Asn33 that contributes to the high affinity of binding [24]. …”
Section: Alkyl Halides In Medicinementioning
confidence: 99%